84.8k views
0 votes
Rearrange the equation so q is the independant variable: -7q+12r=3q-4

r=

User Adhyatmik
by
5.2k points

1 Answer

1 vote

The rearranged equation with q as the independent variable is:

r = (5/6)q - (1/3)

To rearrange the equation so q is the independent variable, we need to isolate r on one side of the equation.

Starting with the given equation:

-7q + 12r = 3q - 4

First, combine the q terms on the left side of the equation:

-7q + 12r = 3q - 4

-10q + 12r = -4

Next, add 10q to both sides of the equation to isolate r:

-10q + 12r = -4

12r = 10q - 4

Finally, divide both sides of the equation by 12 to solve for r:

r = (10q - 4) / 12

Therefore, the rearranged equation with q as the independent variable is:

r = (5/6)q - (1/3)

User Pinpickle
by
4.6k points